Synthesis, optoelectronic, and transistor properties of BODIPY- and cyclopenta[c]thiophene-containing pi-conjugated copolymers - Debnath, Sashi; Singh, Saumya; Bedi, Anjan; Krishnamoorthy, Kothandam; Zade, Sanjio S. (Journal of Physical Chemistry C, 2015)
Three new low-band-gap copolymers were synthesized by fusing dipyrromethene difluoroborane (BODIPY) as the acceptor (A) and thiophene-capped 5,5-bis(hexyloxymethyl)-5,6-dihydro-4H-cyclopenta[c]-thiophene (CPT) as the donor (D). The BODIPY unit was copolymerized through the `alpha' positions (1 and 7 positions) in P1 and through the `beta' positions (2 and 6 positions) in P2 and P3. The additional acetylene unit between D and A in P3 enhanced the conjugation by minimizing the possible steric hindrance compared to that in P2, whereas P1 exhibited a more red-shifted absorption than P2 and P3 because of the more effective conjugaion through the `alpha' positions of BODIPY. Importantly, the optical band gaps (E-g(opt)) obtained from the onset of the absorption spectra are 1.28, 1.71, and 1.57 eV for P1, P2, and P3, respectively. P1 has the lowest band gap for any CPT-containing polymer. In the best transistor devices, a mobility improvement by 4 orders of magnitude from 3.22 x 10(-6) cm(2) V-1 s(-1) for P2 to 0.01 cm(2) V-1 s(-1) for P1 was achieved. DFT calculations alongside measured charge-transport properties indicated that appreciable alterations in the optoelectronic properties of the polymers were achieved through minor changes in their structural features. The polymers were further characterized by thin-film X-ray diffraction, atomic force microscopy, and spectroelectrochemistry to investigate their material and electrochemical properties.

Selenium-containing fused bicyclic heterocycle diselenolodiselenole: field effect transistorstudy and structure property relationship - Debnath, Sashi; Chithiravel, Sundaresan; Sharma, Sagar; Bedi, Anjan; Krishnamoorthy, Kothandam; Zade, Sanjio S. (ACS Applied Materials & Interfaces, 2016)
The first application of the diselenolodiselenole (C4Se4) heterocycle as an active organic field effect transistor materials is demonstrated here. C4Se4 derivatives (2a-2d) were obtained by using a newly developed straightforward diselenocyclization protocol, which includes the reaction of diynes with selenium powder at elevated temperature. C4Se4 derivatives exhibit strong donor characteristics and planar structure (except 2d). The atomic force microscopic analysis and thin-film X-ray diffraction pattern of compounds 2a-2d indicated the formation of distinct crystalline films that contain large domains. A scanning electron microscopy study of compound 2b showed development of symmetrical grains with an average diameter of 150 nm. Interestingly, 2b exhibited superior hole mobility, approaching 0.027 cm(2) V-1 s(-1) with a transconductance of 9.2 mu S. This study correlate the effect of p-stacking, Se center dot center dot center dot Se intermolecular interaction, and planarity with the charge transport properties and performance in the field effect transistor devices. We have shown that the planarity in C4Se4 derivatives was achieved by varying the end groups attached to the C4Se4 core. In turn, optoelectronic properties can also be tuned for all these derivatives by end-group variation.

Site-selective synthesis and characterization of BODIPY-acetylene copolymers and their transistor properties - Debnath, Sashi; Singh, Saumya; Bedi, Anjan; Krishnamoorthy, Kothandam; Zade, Sanjio S. (Journal of Polymer Science Part A-Polymer Chemistry, 2016)
To study the effect of site-selective copolymerization of borondipyrromethene (BODIPY) with acetylene on the structural and optoelectronic properties, three copolymers P1-P3 were synthesized by the Sonogashira cross-coupling of BODIPY units with diacetylene and bromine capping through all the possible linkages: alpha-alpha (P1), alpha-beta (P2), and beta-beta (P3). The optoelectronic properties of the polymers were investigated systematically to understand the effect of site-selective polymerization. The HOMO levels of the polymers were significantly tuned from P1 to P3 with negligible change in the LUMO levels. Broadening of absorption spectra from P3 to P1 was observed because of increase in the extent of conjugation. Additionally, the charge transport properties of these polymers in organic thin-film transistors (OTFTs) revealed that P1 and P3 exhibited only p-type mobility, whereas P2 exhibited electron mobility. Notably, the further investigations of the surface morphology of polymer films by atomic force microscopy (AFM) unveiled that comb like nanostructural arrangements in P3 was beneficial for the charge-carrier mobility over the circular arrangements in P1 and P2. (C) 2016 Wiley Periodicals, Inc.
Keywords: acetylene; BODIPY; DFT; low-band gap

Origin of optoelectronic contradictions in 3,4-cycloalkyl[c]-chalcogenophenes: a computational study - Masilamani, Ganesh; Krishna, Gamidi Rama; Debnath, Sashi; Bedi, Anjan (Polymers, 2023)
The planar morphology of the backbone significantly contributes to the subtle optoelectronic features of pi-conjugated polymers. On the other hand, the atomistic tuning of an otherwise identical pi-backbone could also impact optoelectronic properties systematically. In this manuscript, we compare a series of 3,4-cycloalkylchalcogenophenes by tuning them atomistically using group-16 elements. Additionally, the effect of systematically extending these building blocks in the form of oligomers and polymers is studied. The size of the 3,4-substitution affected the morphology of the oligomers. In addition, the heteroatoms contributed to a further alteration in their geometry and resultant optoelectronic properties. The chalcogenophenes, containing smaller 3,4-cycloalkanes, resulted in lower bandgap oligomers or polymers compared to those with larger 3,4-cycloalkanes. Natural bonding orbital (NBO) calculations were performed to understand the disparity alongside the contour maps of frontier molecular orbitals (FMO).
Keywords: chalcogenophene; DFT calculation; Morphology; optoelectronic properties; steric effect